Effect of Corporate Governance and Corporate Social Responsibility on Financial Performance - Indah Maha Sari; Rita Anugrah; Azwir Nasir (Master of Accounting Universitas Trunojoyo Madura, 2020)
This research was conducted to find out effect of independent commissioner, audit committee, and corporate social responsibility on financial performance at Index Kompas 100 in in Indonesia Stock Exchange period 2016-2018. Index Kompas 100 company has high market capitalization value, so it is suitable for use as a population. Samples were determined using the purposive sampling method. Research using multiple linear analyses. This research prove that independent commissioner, audit committee, corporate social responsibility have a influence on financial performance.